Floristic composition and plant species diversity in and around the brickfield areas of Savar-Dhamrai region of Dhaka district (Jahangirnagar University Journal of Biological Sciences, 2021)
This study has confirmed the occurrence of a total of 181 species of vascular plants under 133 genera and 51 families and estimates the plant species diversity in and around the brickfield areas of Savar-Dhamrai region of Dhaka district. Of these, six species were pteridophytes, 175 were Angiosperms, and 144 species were economically important. Five families, composed of six species, belonged to Pteridophyta, 40 families, consist of 128 species, to Magnoliopsida (dicotyledons) and six families, comprised of 47 species, to Liliopsida (monocotyledons). Total of 161 species were herbs, 14 were shrubs, and only six were trees. Asteraceae with 14 species and Poaceae with 24 species were the largest family in Magnoliopsida and Liliopsida, respectively. Amaranthus L., Persicaria (L.) Mill., Solanum L. and Lindernia All. with four species each were appeared as the best representative genera in Mangoliopsida, while Cyperus L. with five species in Liliopsida. The species composition and diversity of abandoned brickfields were found to be higher than those of functional brickfields. A total of 42 (23.20%) species were common in both abandoned and functional brickfields of this region. Species composition in the abandoned brickfields of Savar and Dhamrai was mostly similar (64.15%). This study suggests to control and monitor the brickfields under the respective authorities to favor the formation and regeneration of natural vegetation in their neighboring areas.Jahangirnagar University J. Biol. Sci. 9(1 & 2): 91-108, 2020 (June & December)